Why does China's stock market have highly synchronous stock price movements? An information supply perspective. Issue 1 (June 2015) - Lin, Karen Jingrong; Karim, Khondkar E.; Carter, Clairmont
Abstract Morck et al. (2000) document that China's stock market is the second most synchronous market in the world, indicating an inferior information environment. These authors conjecture that government quality is associated with cross-sectional variance of information environments across countries, yet evidence on the channels through which government quality affects synchronous security prices is lacking. Our study fills the void and presents a channel for the link between government quality and information environment. We find that low-quality government with weak property rights protection is associated with less supply of firm-specific information. That is, firms ruled by these governments are refrained from disclosing their true performances, causing high stock price synchronicity in China. We also find that firms' hiding activities are affected by firms' political connectedness and external information mediation. Our study contributes to the literature explaining cross-country differences in information environments and its link to the country's political economy.